Antibacterial lyocell fiber and preparation method thereof

By grinding zinc oxide particles into nanoparticle sizes and dispersing them with Lycel fibers, the problem of ordinary Lycel fibers lacking antibacterial function is solved, and the antibacterial properties and original characteristics of the fibers are achieved, and it is suitable for medical and health fields.

CN119777012APending Publication Date: 2025-04-08SHANGHAI LYOCELL FIBER DEV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411977108.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Ordinary lyesel fiber lacks antibacterial function, which limits its application in medical, sanitary products, household products and other fields.

Method used

The zinc oxide particles are ground into nanoparticle sizes and uniformly dispersed with the Lycel fibers in the N-methylmorpholine-N-oxide solvent method to impart excellent antibacterial properties to the fibers.

Benefits of technology

It realizes the antibacterial properties of Lycel fibers, while maintaining the original excellent characteristics of the fibers, such as high humidity modulus, strength and comfort, and is suitable for multiple application scenarios, especially in the medical and health field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an antibacterial lyocell fiber and a preparation method. Nano zinc oxide particles are uniformly dispersed in the lyocell fiber, the particle size of the nano antibacterial zinc oxide particles is 10-100nm, and the mass fraction of the nano antibacterial zinc oxide particles in the fiber is 5%-30%; the wet modulus of the antibacterial lyocell fiber is ≥15cN / dtex. The antibacterial lyocell fiber has a fineness of 1.1-3.3dtex, a dry breaking strength of 3-5cN / dtex, an elongation at break of 8%-20%, and a wet breaking strength of 2.5-5cN / dtex; the zinc oxide content is not less than 10% after washing 100 times. A preparation method for antibacterial lyocell fiber comprises: S1, pretreatment of zinc oxide; S2, mixing the pretreated nano zinc oxide with an NMMO aqueous solution; S3, obtaining a cellulose pre-dissolved pulp; S4, dissolving to obtain a slurry; S5, spinning to obtain the antibacterial lyocell fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of regenerated cellulose fiber materials, and in particular to a lyocell fiber with antibacterial function and a preparation method thereof. Background Art

[0002] As people have higher and higher requirements for the hygiene performance of textiles, the market demand for antibacterial fibers continues to grow. Lyocell fiber, as the third generation of regenerated cellulose fiber, has excellent moisture absorption, comfort and strength, and its application fields are becoming more and more extensive. However, ordinary lyocell fiber lacks antibacterial function, which limits its application in some special fields such as medical, sanitary products, household products, etc. Therefore, the development of lyocell fiber with antibacterial properties has important practical significance and market prospects.

[0003] Antibacterial lyocell fiber achieves its antibacterial property by adding substances with antibacterial function. Most of the antibacterial substances used in the prior art are silver ion type antibacterial agents. However, since alkaline N-methylmorpholine-N-oxide is used as a solvent in the spinning solution during the spinning process of lyocell fiber, the silver ion type antibacterial agent used is easily dissolved in the solvent and oxidized into brown silver oxide, causing the lyocell fiber to change color. The N-methylmorpholine-N-oxide solvent used in the spinning of lyocell fibers is recycled and reused in actual production. The addition of the silver ion type antibacterial agent causes too many impurities in the N-methylmorpholine-N-oxide solvent to be difficult to recover. In addition, there are problems such as the failure of the antibacterial substance resulting in the antibacterial property of the lyocell not being durable. Summary of the invention

[0004] The object of the present invention is to provide an antibacterial lyocell fiber and a preparation method thereof, which imparts excellent antibacterial properties to the fiber by combining zinc oxide with the lyocell fiber while maintaining the original excellent properties of the lyocell fiber.

[0005] The invention provides an antibacterial lyocell fiber. Nano zinc oxide particles are uniformly dispersed in NMMO (N-methylmorpholine-N-oxide) solvent method lyocell fiber. The particle size of the nano antibacterial zinc oxide particles is 10-100nm, and the mass fraction of the nano antibacterial zinc oxide particles in the fiber is 5%-30%. The wet modulus of the antibacterial lyocell fiber is ≥15cN / dtex.

[0006] Furthermore, in an antibacterial lyocell fiber provided by the present invention, the antibacterial lyocell fiber has a fineness of 1.1 to 3.3 dtex, a dry breaking strength of 3 to 5 cN / dtex, an elongation at break of 8% to 20%, and a wet breaking strength of 2.5 to 5 cN / dtex; and the zinc oxide content is not less than 10% after washing 100 times.

[0007] In addition, the present invention also provides a method for preparing any of the above antibacterial lyocell fibers, comprising the following steps:

[0008] S1. Pretreatment of zinc oxide: Grind the zinc oxide particles to nanometer particle size, treat them with a surface modifier under certain conditions, and perform high-speed stirring and ultrasonic dispersion to make them uniformly coated;

[0009] S2, mixing the pretreated nano zinc oxide with the NMMO aqueous solution: uniformly mixing the pretreated zinc oxide particles prepared in step S1 with the NMMO aqueous solution to prepare a NMMO mixed solution containing zinc oxide, wherein the mass content of NMMO in the NMMO aqueous solution is 65% to 87%, the mixing temperature is 60 to 80° C., and the ratio of the pretreated zinc oxide to the NMMO aqueous solution is (0.01 to 0.06):1; the zinc oxide content in the NMMO mixed solution containing nano zinc oxide is 5 to 10%, and the NMMO content in the NMMO aqueous solution is 60 to 80%;

[0010] S3, preparing cellulose pre-dissolved pulp: mixing the aqueous cellulose, the NMMO aqueous solution with a NMMO concentration of 50% to 88%, and the NMMO mixed solution containing zinc oxide prepared in step S2 to obtain a pre-dissolved pulp; the mass ratio of the NMMO mixed solution containing zinc oxide to the aqueous cellulose is 1:(0.20 to 1.00); the mass ratio of the aqueous cellulose to the 50% to 88% NMMO aqueous solution is 1:(2 to 12);

[0011] S4, dissolving to obtain slurry: the pre-dissolved slurry obtained in step S3 is fed into a dissolving machine, heated and vacuumized, and dehydrated, dissolved, homogenized, and defoamed to obtain slurry; the zinc oxide content in the slurry is 1% to 5%;

[0012] S5, spinning to obtain antibacterial lyocell fibers: spinning the slurry obtained in step S4 to obtain antibacterial lyocell fibers.

[0013] Preferably, in the preparation method of antibacterial lyocell fiber provided by the present invention, in step S1, the surface modifier is at least one of a silane coupling agent, a silicone solution or polyethylene glycol; the particle size of nano zinc oxide is ground to 10 to 100 nm, the mass ratio of the surface modifier to the nano zinc oxide is 1:5-1:10, the ultrasonic power is 200 to 500 W, and the stirring speed is 800 to 1500 r / min.

[0014] Preferably, in the method for preparing antibacterial lyocell fiber provided by the present invention, in step S1, the treatment conditions of the surface modifier are first washing and soaking for 0.5 to 10 hours, and then drying at 70 to 120° C. for 0.3 to 2 hours.

[0015] Preferably, in the method for preparing antibacterial lyocell fiber provided by the present invention, in step S3, the preparation of pre-dissolved pulp comprises the steps of:

[0016] (a) Activation: adding cellulose pulp with a degree of polymerization of 300 to 1500 to process water, adjusting the pH value to 4 to 6, adding cellulase for activation; then adding alkali to adjust the pH value to 9 to 13 to terminate the activation, and obtaining pulp porridge;

[0017] (b) pressing: dehydrating the porridge by pressing to obtain hydrous cellulose with a moisture content of 10% to 60%;

[0018] (c) Predissolution: The aqueous cellulose is mixed with a 50% to 88% NMMO aqueous solution and a NMMO mixed solution containing zinc oxide to obtain a predissolved pulp, wherein the mass ratio of the aqueous cellulose to the 50% to 88% NMMO aqueous solution is 1:(3 to 5).

[0019] Further preferably, in the method for preparing antibacterial lyocell fiber provided by the present invention, in step (a), the polymer of cellulose pulp is 500-800, and the mass ratio of hydrous cellulose to 50-88% NMMO aqueous solution is 1:(3.5-4).

[0020] Preferably, in the method for preparing antibacterial lyocell fiber provided by the present invention, in step S4, the cellulose content in the slurry is 11% to 15%, the slurry viscosity is 3000 to 8000 Pa·s, and the slurry refractive index is 1.4830 to 1.4900.

[0021] Preferably, in the preparation method of antibacterial lyocell fiber provided by the present invention, in step S5, the spinning parameters are: spinning speed 35-100 m / min, spinning air gap 5-50 mm, spinning air temperature 10-30°C, spinning air flow rate 100-500 L / H, air relative humidity 50-80%, coagulation bath concentration 10-30%, and coagulation bath temperature 5-30°C.

[0022] In addition, the present invention also provides the use of any of the above antibacterial lyocell fibers to make yarns, fabrics, clothing, and non-woven fabrics.

[0023] The advantages of the present invention are mainly reflected in: (1) After the zinc oxide particles are ground, the surface is modified under certain conditions. By controlling the particle size, processing conditions, selecting a suitable surface modifier and other measures, the surface polarity and specific surface area of ​​the zinc oxide particles are increased, thereby improving the dispersibility and compatibility. (2) The modified zinc oxide particles are mixed with an NMMO aqueous solution with a mass concentration of 65%-87%. Because NMMO is amphiphilic, by selecting a suitable ratio, NMMO and the modified zinc oxide powder have a strong interaction, which makes it easier to disperse and not agglomerate in the cellulose solution. (3) Before dissolution, a pre-dissolution step is added, and the addition of zinc oxide solution and the premixing of cellulose and NMMO solution are achieved by using a device with a shearing effect, thereby maintaining the best dispersion effect. Due to the presence of a certain viscosity, the dissolved slurry can still maintain the dispersed state of the zinc oxide powder, and excess water is removed under vacuum conditions, thereby achieving the effective addition of functional zinc oxide powder. (4) The zinc oxide content in antibacterial lyocell fiber is 5% to 30%, the fiber fineness is 1.1 to 3.3 dtex, the dry and wet strength is high, the elongation at break is 8% to 20%, and it has a high wet modulus, which is ≥15 cN / dtex. The zinc oxide content in the fiber is high and evenly distributed. After washing 20 times, 50 times, and 100 times, the zinc oxide content is still as high as 10%. Therefore, the fiber made is suitable for multiple application scenarios, especially in the medical and health fields. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with embodiments, but the present invention is not limited to the following embodiments, and any technical solutions implemented by modifications, replacements or changes based on the technical basic ideas of the present invention belong to the scope of the present invention.

[0025] Adding zinc oxide to the fiber can make the fiber have a series of characteristics such as antibacterial and antibacterial, UV protection, deodorization and enzyme resistance. However, due to the characteristics of large specific surface area and large specific surface energy, nano ZnO is easy to agglomerate itself; on the other hand, nano zinc oxide has strong surface polarity and is not easy to be evenly dispersed in organic media. There have always been difficult to overcome technical problems in fiber production, especially difficult to add to Lyocell fiber. The present invention first grinds zinc oxide particles and then performs surface modification under certain conditions, and increases the surface polarity and specific surface area of ​​zinc oxide particles by controlling particle size, processing conditions, selecting suitable surface modifiers and other measures, thereby improving dispersibility and compatibility. Then, combined with the process characteristics of NMMO solvent-based lyocell fiber, a distribution mixing method is adopted in which the pretreated zinc oxide is mixed with an NMMO aqueous solution, and then a cellulose-containing pre-dissolved pulp is prepared, and then the purpose of preparing high-quality antibacterial lyocell fiber is achieved by controlling the ratio of zinc oxide, cellulose, NMMO and water in each step.

[0026] The solvent-based antibacterial lyocell fiber preparation method of the present invention comprises the following steps:

[0027] S1. Pretreatment of zinc oxide: It includes ball-milling nano zinc oxide to a particle size of 10-100 nm, and treating it with a silane coupling agent or an organic silicon solution or polyethylene glycol under certain conditions, and uniformly coating it by combining high-speed stirring and ultrasonic dispersion to improve dispersibility and compatibility.

[0028] S2. Mixing of pretreated zinc oxide and NMMO aqueous solution: The pretreated zinc oxide powder is evenly mixed with a NMMO aqueous solution having a mass concentration of 65%-87% to obtain a NMMO mixed solution containing zinc oxide. The mixing temperature is 60-80°C, the ratio of nano zinc oxide to NMMO aqueous solution is (0.01-0.06):1, and the pH value is 10-12.

[0029] S3. Preparation of cellulose-containing pre-dissolved pulp. Aqueous cellulose pulp, a 50-88% NMMO aqueous solution, and a NMMO solution containing zinc oxide are stirred and mixed to obtain pre-dissolved pulp.

[0030] S4, dissolving to obtain slurry. The pre-dissolved slurry is sent to a dissolving machine, heated and vacuumed, and then dehydrated, dissolved, homogenized, and defoamed to obtain slurry.

[0031] S5, spinning: Spinning is performed using the slurry to obtain zinc oxide antibacterial lyocell fiber.

[0032] S6, post-processing: washing, oiling, drying and other steps.

[0033] Regarding step S1 "pretreatment of zinc oxide". The specific steps include ball-milling the nano zinc oxide to a particle size of 10-100nm, treating it with a silane coupling agent or silicone solution or polyethylene glycol, washing and soaking for 0.5-10 hours, and then drying it at 70-120°C for 0.3-2 hours, and uniformly coating it by combining high-speed stirring and ultrasonic dispersion. The mass ratio of dispersant to nano zinc oxide is 1:5-1:10, the ultrasonic power is 200-500W, and the stirring speed is 800-1500rpm. By selecting a comprehensive technical means such as suitable particle size, dispersant, dispersant treatment conditions and process, the surface polarity of zinc oxide particles is changed, the specific surface area is increased, and thus the dispersibility and compatibility are improved.

[0034] Regarding step S2 "mixing of pretreated zinc oxide and NMMO aqueous solution". The pretreated zinc oxide powder is evenly mixed with a NMMO aqueous solution with a mass concentration of 65%-87%, and the mixing temperature is 60-80°C; the ratio of nano zinc oxide to NMMO aqueous solution is (0.01-0.06):1. Because NMMO is amphiphilic, it has a strong interaction with the pretreated zinc oxide powder and is easier to disperse without agglomeration in the cellulose solution; the NMMO solvent mixture containing nano zinc oxide contains 5-10% zinc oxide and 60-80% NMMO aqueous solution.

[0035] Regarding step S3 "preparation of cellulose-containing pre-dissolved pulp". The aqueous cellulose, NMMO aqueous solution and NMMO mixed solution containing zinc oxide are stirred to obtain pre-dissolved pulp. It can be divided into the following steps: pulp activation, pressing, pre-dissolution, etc. The details are as follows:

[0036] (a) Activation: adding pulp with a degree of polymerization of 300 to 1000 to process water, adjusting the pH value to 4 to 6, adding cellulase for activation; then adding alkali to adjust the pH value to 9 to 13 to terminate the activation, and obtaining pulp porridge;

[0037] (b) pressing: dehydrating the porridge obtained in the previous step by pressing to obtain hydrous cellulose with a moisture content of 10 to 60%;

[0038] (c) pre-dissolution: mixing aqueous cellulose with a 50-88% N-methylmorpholine-N-oxide aqueous solution and a NMMO solvent mixture containing nano zinc oxide to obtain a pre-dissolved pulp;

[0039] Wherein, in step (a), the pulp polymerization degree is selected to be 300-1000, preferably 500-800. The activation process is simple, and less chemical reagents are added. The process is as follows: prepare process water → add pulp → adjust pH value → add cellulase → terminate activation. Pulp polymerization degree of 500-800 is conducive to the activation of cellulase between pH values ​​4-6. When the pulp polymerization degree exceeds 1000, the viscosity of the zinc oxide functional cellulose slurry is large, which is not conducive to subsequent slurry transportation; when the pulp polymerization degree is less than 500, the viscosity of the zinc oxide functional cellulose slurry is small, the spinnability is poor, the spinning cannot be formed or the fiber strength is low. During the pulp activation process, appropriate reuse of process water and adjustment of pH value are conducive to the action of cellulase. Preferably, the cellulase is liquid cellulase and / or ligninase.

[0040] Wherein, in step (b), vacuum dehydration pressing can be used to improve the dehydration efficiency, and the pressing moisture content is 10-60%.

[0041] Wherein, in step (c), the NMMO mixed solution containing nano zinc oxide is pre-dissolved with aqueous cellulose and NMMO aqueous solution to obtain a pre-dissolved slurry. The NMMO aqueous solution is used to pre-disperse the zinc oxide particles, and then the zinc oxide particles are pre-dispersed with the aqueous cellulose and NMMO aqueous solution to achieve effective dispersion and addition of the zinc oxide particles and prevent the agglomeration and sedimentation of the zinc oxide particles by using similar solvents. Preferably, the mass ratio of aqueous cellulose to 50-88% N-methylmorpholine-N-oxide aqueous solution is 1: (2-12), preferably 1: (3-5), and more preferably 1: (3.5-4). The use of 50-88% by mass N-methylmorpholine-N-oxide aqueous solution is not only conducive to pulp swelling, but also conducive to uniform dissolution and slurry stability. Only when the slurry quality is improved can high-quality finished products be made. If the N-methylmorpholine-N-oxide aqueous solution is used at a concentration of less than 50%, the dissolution equipment will be overburdened during the dissolution in the lower stage, exceeding the equipment design capacity, and the slurry cannot be dissolved. In addition, the low concentration will increase the power consumption and steam energy consumption during the dissolution. The N-methylmorpholine-N-oxide aqueous solution with a concentration of more than 88% is not yet technically feasible at home and abroad. At the same time, the ratio also needs to be controlled. If the mass ratio of aqueous cellulose to N-methylmorpholine-N-oxide aqueous solution is higher than 1:2, the slurry cannot be completely dissolved. If the mass ratio of aqueous cellulose to N-methylmorpholine-N-oxide aqueous solution is lower than 1:12, the slurry has low viscosity and cannot be spun into shape.

[0042] Regarding step S4 "dissolving to obtain dissolving slurry". The dissolving machine parameters are set to vacuum degree 1.0 kPa to 15 kPa, temperature 60 to 120°C. The cellulose content is 11% to 15%, the slurry viscosity is 3000 to 8000 Pa·s, and the slurry refractive index is 1.4830 to 1.4900. The slurry is observed under a microscope, and no obvious insoluble gel particles are found, and the zinc oxide particles are evenly dispersed.

[0043] Regarding step S5 "spinning". The slurry is transported by a booster pump, enters a metering pump, and is ejected through a spinneret to form a dry-wet spinning process. The spinning speed is 35-100 m / min, the spinning air gap is 5-50 mm, the spinning air temperature is 10-30 ° C, the spinning air flow rate is 100-500 L / H, the relative humidity of the air is 50%-80%, the coagulation bath concentration is 10%-30%, and the coagulation bath temperature is 5-30 ° C.

[0044] Regarding step S6 "post-processing", it includes washing, oiling and drying.

[0045] The water washing is to transport the spun fibers to a water washing bath at 20-80°C for washing. Preferably, deionized water can be used for washing. After the fibers are washed with water, the solvent N-methylmorpholine-N-oxide can be recovered, thereby increasing the recovery rate of the solvent.

[0046] Oiling refers to the oiling treatment of washed fibers, with an oiling concentration of 0.5% to 5%, an oiling pH of 6 to 9, and an oiling temperature of 20 to 80°C. Preferably, the oiling agent can be selected from a three-component combination of LeminOR, LeminWG and LeminAN produced by the manufacturer CLARIANT, and the oiling agent is applied at a pH of 6 to 9 and a temperature of 80°C. Preferably, the drying temperature is 80 to 150°C.

[0047] Example 1

[0048] The zinc oxide particles are ground to 10nm, treated with a silane coupling agent, washed and soaked for 0.5 hours, and then dried at 100°C for 1 hour. The particles are uniformly coated by combining high-speed stirring and ultrasonic dispersion. The mass ratio of the dispersant to nano zinc oxide is 1:5-1:10. The ultrasonic power is 200-500W and the stirring speed is 800-1500rpm.

[0049] The zinc oxide powder is mixed evenly with a NMMO aqueous solution with a mass concentration of 75% to obtain a NMMO mixed solution containing zinc oxide. The mixing temperature is 60-80° C., the ratio of nano zinc oxide to the NMMO aqueous solution is (0.01-0.06):1, and the pH value is 10.

[0050] The aqueous cellulose is mixed with a 50-88% N-methylmorpholine-N-oxide aqueous solution and a NMMO mixed solution containing a nano zinc oxide solvent to obtain a pre-dissolved pulp; the NMMO mixed solution containing nano zinc oxide contains 5-10% zinc oxide and the NMMO aqueous solution contains 60-80% NMMO.

[0051] Add pulp with a degree of polymerization of 500 to a 2 , pH value 6.8, temperature 50 ℃ process water, adjust the pH value to 5, add ligninase to activate for one hour, add sodium hydroxide to terminate the activation, and adjust the pH value to 10.5; after the activation is terminated, the pulp porridge is vacuum dehydrated and pressed, and the water content of the hydrous cellulose is controlled to be 48%; then, the NMMO mixed solution containing zinc oxide and 81% N-methylmorpholine-N-oxide aqueous solution are added into the pressed pulp porridge, wherein the mass ratio of the hydrous cellulose to the NMMO mixed solution containing zinc oxide is 1:0.22, and the mass ratio of the hydrous cellulose to the NMMO aqueous solution is 1:3.8, and the pre-dissolved pulp is obtained after the pulp is swollen; the outlet temperature of the pre-dissolved pulp is 70 ℃, and the pre-dissolved pulp composition is: cellulose 9.9%, pH value 9.5.

[0052] The pre-dissolved pulp is sent to the dissolving machine, heated and vacuumed, and then dehydrated, dissolved, homogenized, and defoamed to obtain a slurry; the dissolving machine parameters are set to a vacuum degree of 1.0kpa-15kpa and a temperature of 60-120°C; the cellulose content in the slurry is 11%-15%, the zinc oxide content is 2%, the slurry viscosity is 3000Pa·s, and the slurry refractive index is 1.4830-1.4900. The slurry is observed under a microscope, and there are no obvious insoluble gel particles, and the zinc oxide particles are evenly dispersed.

[0053] The slurry is transported to a filter, filtered to remove impurities in the pulp raw material, and then transported by a booster pump, ejected through a spinneret, and formed by dry-wet spinning, with a spinning speed of 50 m / min, a spinning air gap of 10 mm, a spinning blowing temperature of 14°C, a spinning blowing flow rate of 250 L / H, a blowing relative humidity of 50%, a coagulation bath concentration of 15%, a coagulation bath temperature of 10°C, and the fiber is washed with water at a washing temperature of 60°C; the washed fiber is oiled with an oil agent circulation concentration of 1.0%, an oil agent circulation pH value of 6.5, and an oil agent circulation temperature of 50°C; the oiled fiber is dried at 100°C to obtain a finished fiber.

[0054] The test results of the antibacterial lyocell fiber properties are as follows: fineness 1.67 dtex, dry breaking strength 3.70 cN / dtex, wet breaking strength 3.00 cN / dtex, dry breaking elongation 15.8%, wet breaking elongation 18.2%, wet modulus 15.4 cN / dtex, dry strength variation coefficient 10%, whiteness 68%, oil content 0.23%, regain 11.2%, zinc oxide content 10%.

[0055] Example 2

[0056] The zinc oxide particles are ground to 20 nm, treated with polyethylene glycol, washed and soaked for 1 hour, and then dried at 100°C for 2 hours. The particles are uniformly coated by combining high-speed stirring and ultrasonic dispersion. The mass ratio of the dispersant to nano zinc oxide is 1:5-1:10. The ultrasonic power is 200-500W and the stirring speed is 800-1500r / min.

[0057] The zinc oxide powder is mixed evenly with a 60% NMMO aqueous solution to obtain a zinc oxide mixed solution. The mixing temperature is 60-80° C., the ratio of nano zinc oxide to the NMMO aqueous solution is (0.01-0.06):1, and the pH value is 11.

[0058] The pre-dissolved pulp is obtained by mixing the aqueous cellulose with a 50-88wt% NMMO aqueous solution and a NMMO mixed solution containing nano zinc oxide; the NMMO mixed solution containing nano zinc oxide is an aqueous solution containing 5-10wt% zinc oxide and 60-80wt% NMMO.

[0059] Add the pulp with degree of polymerization of 800 to the conductivity of <5μs / cm 2 , pH value 7, temperature 50 ℃ process water, adjust the pH value to 5, add cellulase to activate for one hour, add sodium hydroxide to terminate the activation, and adjust the pH value to 10.5; after the activation is terminated, the pulp porridge is vacuum dehydrated and pressed, and the water content of the hydrous cellulose is controlled to be 48wt%; then the pressed pulp porridge is added to a mixed solution containing zinc oxide and 81wt% NMMO, wherein the mass ratio of the hydrous cellulose to the zinc oxide-containing NMMO mixed solution is 1:0.5, and the mass ratio of the hydrous cellulose to the NMMO aqueous solution is 1:8, and the pre-dissolved pulp is obtained after the pulp is swollen; the outlet temperature of the pre-dissolved pulp is 70 ℃, the pre-dissolved pulp composition: cellulose 10%, pH value 9.5.

[0060] The pre-dissolved pulp is sent to the dissolving machine, heated and vacuumed, and then dehydrated, dissolved, homogenized, and defoamed to obtain a slurry; wherein the dissolving machine parameters are set to a vacuum degree of 10 kPa and a temperature of 60-120°C. The cellulose content in the slurry is 11%-15%, the zinc oxide content is 8%, the slurry viscosity is 5000 Pa·s, and the slurry refractive index is 1.4830-1.4900. When the slurry is observed under a microscope, there are no obvious insoluble gel particles, and the zinc oxide particles are evenly dispersed.

[0061] The slurry is transported to a filter, filtered to remove impurities in the pulp raw material, and then transported by a booster pump, sprayed out through a spinneret, and formed by dry-wet spinning, with a spinning speed of 40 m / min, a spinning air gap of 10 mm, a spinning blowing temperature of 15° C., a spinning blowing flow rate of 250 L / H, a blowing relative humidity of 50%, a coagulation bath concentration of 20%, a coagulation bath temperature of 10° C., and the fiber is washed with water at a washing temperature of 60° C. The washed fiber is oiled at an oil agent circulation concentration of 1.0%, an oil agent circulation pH value of 6.5, and an oil agent circulation temperature of 50° C. The oiled fiber is dried at 100° C. to obtain a finished fiber.

[0062] The test results of the antibacterial lyocell fiber properties are as follows: fineness 2.2dtex, dry breaking strength 3.50cN / dtex, wet breaking strength 2.90cN / dtex, dry breaking elongation 15.8%, wet breaking elongation 18.2%, wet modulus 15.4cN / dtex, dry strength variation coefficient 10%, whiteness 68%, oil content 0.23%, regain 11.2%, zinc oxide content 20%.

[0063] Example 3

[0064] The zinc oxide particles are ground to 100nm, treated with silicone solution, washed and soaked for 2 hours, and then dried at 100℃ for 2 hours. The particles are evenly coated by combining high-speed stirring and ultrasonic dispersion. The mass ratio of dispersant to nano zinc oxide is 1:5-1:10. The ultrasonic power is 200-500W and the stirring speed is 800-1500r / min.

[0065] The zinc oxide powder is mixed evenly with an NMMO aqueous solution with a mass concentration of 85% to obtain a zinc oxide mixed solution. The mixing temperature is 60-80° C., the ratio of nano zinc oxide to the NMMO aqueous solution is (0.01-0.06):1, and the pH value is 12.

[0066] The pre-dissolved pulp is obtained by mixing the aqueous cellulose with a 50% to 88% NMMO aqueous solution and a NMMO mixed solution containing nano zinc oxide; the NMMO mixed solution containing nano zinc oxide contains 5% to 10% zinc oxide and 60% to 80% NMMO aqueous solution.

[0067] Add pulp with a degree of polymerization of 1000 to a 2 , pH value 7, temperature 50 ℃ process water, adjust pH value to 5, add cellulase to activate for one hour, add sodium hydroxide to stop activation, adjust pH value to 10.5; after activation is stopped, the pulp porridge is vacuum dehydrated and squeezed, and the water content of the hydrous cellulose is controlled to be 48%. The squeezed pulp porridge is put into the NMMO mixed solution containing zinc oxide and 60% NMMO aqueous solution, the mass ratio of hydrous cellulose to the NMMO mixed solution containing zinc oxide is 1:0.5, and the mass ratio of hydrous cellulose to the NMMO aqueous solution is 1:8. After the pulp is swollen, the pre-dissolved pulp is obtained; the outlet temperature of the pre-dissolved pulp is 70 ℃, the pre-dissolved pulp composition: cellulose 10%, pH value 9.5.

[0068] The pre-dissolved pulp is sent to the dissolving machine, heated and vacuumed, and then dehydrated, dissolved, homogenized, and defoamed to obtain a slurry. The dissolving machine parameters are set to a vacuum degree of 10 kPa and a temperature of 60-120°C. The cellulose content in the slurry is 11%-15%, the zinc oxide content is 8%, the slurry viscosity is 5000 Pa·s, and the slurry refractive index is 1.4830-1.4900. When the slurry is observed under a microscope, there are no obvious insoluble gel particles, and the zinc oxide particles are evenly dispersed.

[0069] The slurry is transported to a filter, filtered to remove impurities in the pulp raw material, and then transported by a booster pump, ejected through a spinneret, and formed by dry-wet spinning, with a spinning speed of 40 m / min, a spinning air gap of 10 mm, a spinning blowing temperature of 15°C, a spinning blowing flow rate of 250 L / H, a blowing relative humidity of 50%, a coagulation bath concentration of 20%, a coagulation bath temperature of 10°C, and the fiber is washed with water at a washing temperature of 60°C; the washed fiber is oiled with an oil agent circulation concentration of 1.0%, an oil agent circulation pH value of 6.5, and an oil agent circulation temperature of 50°C; the oiled fiber is dried at 100°C to obtain a finished fiber.

[0070] The test results of the antibacterial lyocell fiber properties are as follows: fineness is 1.33dtex, dry breaking strength is 3.38cN / dtex, wet breaking strength is 2.78cN / dtex, dry breaking elongation is 15.8%, wet breaking elongation is 18.2%, wet modulus is 12.8cN / dtex, dry strength variation coefficient is 10%, whiteness is 68%, oil content is 0.23%, regain is 11.2%, and zinc oxide content is 15%.

[0071] Comparative Example 1

[0072] Add the pulp with degree of polymerization of 800 to the conductivity of <5μs / cm 2 , pH value 6.8, temperature 50 ℃ process water, adjust pH value to 5, add ligninase activation for one hour, add sodium hydroxide to stop activation, adjust pH value to 10.5; after activation is stopped, the pulp porridge is vacuum dehydrated and squeezed, and the water content of hydrous cellulose is controlled to be 48wt%. Then the squeezed porridge slurry (hydrous cellulose) is added to a NMMO mixed solution containing zinc oxide (without pretreatment) and an 81wt% NMMO aqueous solution, wherein the mass ratio of hydrous cellulose to the NMMO mixed solution containing zinc oxide is 1:0.22, and the mass ratio of hydrous cellulose to the NMMO aqueous solution is 1:3.8, and the pre-dissolved pulp is obtained after the pulp is swollen; the outlet temperature of the pre-dissolved pulp is 70 ℃, and the pre-dissolved pulp composition is: cellulose 9.9%, pH value 9.5.

[0073] The pre-dissolved pulp is sent to the dissolving machine, heated and vacuumed, and then dehydrated, dissolved, homogenized, and defoamed to obtain a slurry. The dissolving machine parameters are set to a vacuum degree of 1.0kpa to 15kpa and a temperature of 60 to 120°C. The cellulose content in the slurry is 11% to 15%, the zinc oxide content is 2%, the slurry viscosity is 5000Pa·s, and the slurry refractive index is 1.4830 to 1.4900. When the slurry is observed under a microscope, zinc oxide particles are agglomerated and insoluble gel particles exist.

[0074] The slurry is transported to a filter, filtered to remove impurities in the pulp raw material, and then transported by a booster pump, ejected through a spinneret, and formed by dry-wet spinning, with a spinning speed of 30 m / min, a spinning air gap of 10 mm, a spinning blowing temperature of 14°C, a spinning blowing flow of 250 L / H, a blowing relative humidity of 50%, a coagulation bath concentration of 15%, a coagulation bath temperature of 10°C, and the fiber is washed with water at a washing temperature of 60°C; the washed fiber is oiled with an oil agent circulation concentration of 1.0%, an oil agent circulation pH value of 6.5, and an oil agent circulation temperature of 50°C; the oiled fiber is dried at 100°C to obtain a finished fiber.

[0075] The fiber test results are as follows: fineness is 3.3dtex, dry breaking strength is 2.5cN / dtex, wet breaking strength is 1.8cN / dtex, dry breaking elongation is 16%, wet breaking elongation is 18.2%, wet modulus is 8cN / dtex, dry strength variation coefficient is 20%, whiteness is 68%, oil content is 0.23%, regain is 11.2%, zinc oxide content: 2-5%.

[0076] Since the zinc oxide particles are not surface modified and are directly added to the pre-dissolved slurry, there are particles in the spinning slurry, the spinning speed is as low as 30m / min, and the broken and floating fibers are serious, with a dry breaking strength as low as 2.5cN / dtex.

[0077] The functional test results of the solvent-processed antibacterial zinc oxide lyocell fibers produced in Examples 1 to 3 and the fiber produced in Comparative Example 1 are summarized and compared in Table 1.

[0078] Table 1 Functional test results of the products of Examples 1 to 3 and Comparative Example 1

[0079]

[0080] Conclusion: The antibacterial lyocell fiber prepared by the method of the present invention has a zinc oxide content that is stable at more than 10% and has a high wet modulus, which is ≥12cN / dtex, and the dry breaking strength and wet breaking strength of the fiber are high. In Comparative Example 1, since the zinc oxide particles are not surface-modified and directly added to the pre-dissolved slurry, there are particles in the spinning slurry, the spinning speed is as low as 30m / min, and the broken and floating filaments are serious, and the dry breaking strength is as low as 2.5cN / dtex. The zinc oxide content in the fiber is high and evenly distributed. After washing 20 times, 50 times, and 100 times, the zinc oxide content is still as high as 10%.

[0081] Therefore, the antibacterial lyocell fiber prepared by the present invention is suitable for multiple application scenarios, especially in the medical and health fields.

Claims

1. An antibacterial lyocell fiber, characterized in that: Nano zinc oxide particles are uniformly dispersed in NMMO (N-methylmorpholine-N-oxide) solvent-processed lyocell fibers. The particle size of the nano antibacterial zinc oxide particles is 10 to 100 nm, and the mass fraction of the nano antibacterial zinc oxide particles in the fibers is 5% to 30%. The wet modulus of the antibacterial lyocell fibers is ≥15 cN / dtex.

2. An antibacterial lyocell fiber as claimed in claim 1, characterized in that: The antibacterial lyocell fiber fineness 1.1~3.3dtex, dry breaking strength 3~5cN / dtex, elongation at break 8%~20%, wet breaking strength 2.5~5cN / dtex; After washing 100 times, the zinc oxide content is not less than 10%.

3. The method for preparing an antibacterial lyocell fiber according to any one of claims 1 to 2, characterized in that The following steps are involved: S1. Pretreatment of zinc oxide: Grind the zinc oxide particles to nanometer particle size, treat them with a surface modifier under certain conditions, and perform high-speed stirring and ultrasonic dispersion to make them uniformly coated; S2, mixing the pretreated nano zinc oxide with the NMMO aqueous solution: uniformly mixing the pretreated zinc oxide particles obtained in step S1 with the NMMO aqueous solution to obtain a NMMO mixed solution containing zinc oxide, wherein the mass content of NMMO in the NMMO aqueous solution is 65% to 87%, the mixing temperature is 60 to 80° C., and the ratio of the pretreated zinc oxide to the NMMO aqueous solution is (0.01 to 0.06):1; the zinc oxide content in the NMMO mixed solution containing nano zinc oxide is 5 to 10%, and the NMMO content in the NMMO aqueous solution is 60 to 80%; S3, preparing cellulose pre-dissolved pulp: mixing the aqueous cellulose, the NMMO aqueous solution with a NMMO concentration of 50% to 88%, and the NMMO mixed solution containing zinc oxide prepared in step S2 to obtain a pre-dissolved pulp; the mass ratio of the NMMO mixed solution containing zinc oxide to the aqueous cellulose is 1:(0.20 to 1.00); the mass ratio of the aqueous cellulose to the 50% to 88% NMMO aqueous solution is 1:(2 to 12); S4, dissolving to obtain slurry: feeding the pre-dissolved slurry obtained in step S3 into a dissolving machine, heating and vacuumizing, dehydrating, dissolving, homogenizing, and defoaming to obtain slurry; the zinc oxide content in the slurry is 1% to 5%; S5, spinning to obtain antibacterial lyocell fibers: spinning the slurry obtained in step S4 to obtain antibacterial lyocell fibers.

4. The method for preparing an antibacterial lyocell fiber according to claim 3, characterized in that: In the step S1, the surface modifier is at least one of a silane coupling agent, an organosilicon solution, or polyethylene glycol; the particle size of the nano zinc oxide is ground to 10 to 100 nm, the mass ratio of the surface modifier to the nano zinc oxide is 1:5-1:10, the ultrasonic power is 200 to 500 W, and the stirring speed is 800 to 1500 r / min.

5. The method for preparing an antibacterial lyocell fiber according to claim 3, characterized in that: In the step S1, the treatment conditions are first washing and soaking for 0.5 to 10 hours, and then drying at 70 to 120° C. for 0.3 to 2 hours.

6. The method for preparing an antibacterial lyocell fiber according to claim 3, characterized in that: In step S3, the preparation of the pre-dissolved pulp includes the following steps: (a) Activation: adding cellulose pulp with a degree of polymerization of 300 to 1500 to process water, adjusting the pH value to 4 to 6, adding cellulase for activation; then adding alkali to adjust the pH value to 9 to 13 to terminate the activation, and obtaining pulp porridge; (b) pressing: dehydrating the porridge by pressing to obtain hydrous cellulose with a moisture content of 10% to 60%; (c) Predissolution: The aqueous cellulose is stirred and mixed with a 50% to 88% NMMO aqueous solution and a NMMO mixed solution containing zinc oxide to obtain a predissolved pulp, wherein the mass ratio of the aqueous cellulose to the 50% to 88% NMMO aqueous solution is 1:(3 to 5).

7. The method for preparing an antibacterial lyocell fiber according to claim 6, characterized in that: The polymer content of the cellulose pulp in step (a) is 500-800, and the mass ratio of the hydrous cellulose to the 50-88% NMMO aqueous solution is 1:(3.5-4).

8. The method for preparing an antibacterial lyocell fiber according to claim 3, characterized in that: In the step S4, the cellulose content in the slurry is 11% to 15%, the viscosity of the slurry is 3000 to 8000 Pa·s, and the refractive index of the slurry is 1.4830 to 1.4900.

9. The method for preparing an antibacterial lyocell fiber according to claim 3, characterized in that: In step S5, the spinning parameters are: spinning speed 35-100 m / min, spinning air gap 5-50 mm, spinning air temperature 10-30°C, spinning air flow 100-500 L / H, air relative humidity 50-80%, coagulation bath concentration 10-30%, and coagulation bath temperature 5-30°C.

10. The use of any one of claims 1 to 2, characterized in that the antibacterial lyocell fiber Made into yarn, fabrics, clothing, and non-woven fabrics.